Extracting sub-cycle electronic and nuclear dynamics from high harmonic spectra - Austin, Dane R.; Johnson, Allan S.; Mcgrath, Felicity; Wood, David; Miseikis, Lukas; Siegel, Thomas; Hawkins, Peter; Harvey, Alex; Masin, Zdenek; Patchkovskii, Serguei; Vacher, Morgane; Malhado, Joao Pedro; et al. (Scientific Reports, 2021)
We present a new methodology for measuring few-femtosecond electronic and nuclear dynamics in both atoms and polyatomic molecules using multidimensional high harmonic generation (HHG) spectroscopy measurements, in which the spectra are recorded as a function of the laser intensity to form a two-dimensional data set. The method is applied to xenon atoms and to benzene molecules, the latter exhibiting significant fast nuclear dynamics following ionization. We uncover the signature of the sub-cycle evolution of the returning electron flux in strong-field ionized xenon atoms, implicit in the strong field approximation but not previously observed directly. We furthermore extract the nuclear autocorrelation function in strong field ionized benzene cations, which is determined to have a decay of τ= 4 ± 1 fs, in good agreement with the τ= 3.5 fs obtained from direct dynamics variational multi-configuration Gaussian calculations. Our method requires minimal assumptions about the system, and is applicable even to un-aligned polyatomic molecules.
CRIS-Team Scopus Importer:2023-04-20